Design and fabrication of a novel XYθz monolithic micro-positioning stage driven by NiTi shape-memory-alloy actuators - AbuZaiter, A. (Institute of Physics Publishing, 2016)
This paper reports a new shape-memory-alloy (SMA) micro-positioning stage. The device has been monolithically micro-machined with a single fabrication step. The design comprises a moving stage that is manipulated by six SMA planar springs actuators to generate movements with three degrees of freedom. The overall design is square in shape and has dimensions of 12 mm ×12 mm ×0.25 mm. Localized thermomechanical training for shape setting of SMA planar springs was performed using electrical current induced heating at restrained condition to individually train each of the six actuators to memorize a predetermined shape. For actuation, each SMA actuator is individually driven using Joule heating induced by an electrical current. The current flow is controlled by an external pulse-width modulation signal. The thermal response and heat distribution were simulated and experimentally verified using infrared imaging. The micro-positioning results indicated maximum stage movements of 1.2 and 1.6 mm along the x- and y-directions, respectively. Rotational movements were also demonstrated with a total range of 20°. The developed micro-positioning device has been successfully used to move a small object for microscopic scanning applications.